Menakar Minat Beli Tiket Sepakbola Pengguna Aplikasi Mobile PSISFC+ Berbasis Persepsi Kemanfaatan dan Persepsi Kemudahan - Kurniawati, Emaya; Sukmawan, Satria (Badan Riset dan Inovasi Daerah Kota Semarang, 2025)
The research aims to measure the interest in buying football tickets of PSISFC+ mobile application users based on the perception of usefulness and convenience in Semarang City. The method used in the study is quantitative. Sampling using the purposive sampling method so that the number of samples in this study was 85 respondents obtained from the results of distributing questionnaires to respondents via Google forms. Data analysis used the Partial Least Square (PLS) approach assisted by SmartPLS software version 3.29. IBM SPSS 26 software. The number of research samples was 85 PSIS football supporters. The results of the research show that partially there is a positive and significant influence between the perception of usefulness and the perception of convenience on the interest in buying football tickets of PSISFC+ mobile application users in Semarang City. Simultaneously there is a positive and significant influence between the perception of usefulness and the perception of convenience on the interest in buying football tickets of PSISFC+ mobile application users in Semarang City.Kata Kunci: benefits,Â convenience, interest, PSIS